2019
DOI: 10.1002/mmce.21879
|View full text |Cite
|
Sign up to set email alerts
|

Filtennas for wireless application: A review

Abstract: In recent year, various filtenna circuits have been developed satisfying the objectives and prerequisites of wireless communication. Some of these developed designs are new or some are the improved version of previous works whereas the others are the combination of conventional methods. This article presents the review of filtenna circuits starting from the beginning to the improvements until date. This article starts with brief overview of various filters with their design strategies and ends in its implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Therefore, for space minimization, the concept of integrating both the antenna and filter in a single structure appears as a potential solution, and it is known as filter-antenna or filtenna. In the literature, several approaches containing filtennas have been discussed [6][7][8]. Some authors suggested more than one CR antenna designed separately at the same substrate, an antenna for communication and another for sensing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for space minimization, the concept of integrating both the antenna and filter in a single structure appears as a potential solution, and it is known as filter-antenna or filtenna. In the literature, several approaches containing filtennas have been discussed [6][7][8]. Some authors suggested more than one CR antenna designed separately at the same substrate, an antenna for communication and another for sensing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The filtenna integrates filters into the antenna system. 23 Recently, the reconfigurable band-notch antenna system is gaining the attention of antenna researchers because it aids in minimizing system interference. 24 Such reconfiguration can be made by using different switches like PIN diodes, optically controlled switches, and RF-MEMS.…”
Section: Introductionmentioning
confidence: 99%
“…A dual band circularly polarized DRA is presented in Reference 12 which covers the important operating band (27.5‐28.35 GHz) for future 5G MMW communication systems. In addition, several filtenna designs have been reported in Reference 13 for recent wireless communications. Planar filtenna structures can be formed based on either defected ground structure or resonator or SIW filter.…”
Section: Introductionmentioning
confidence: 99%